Pengaruh Pembiasaan Sholat Duha Berjamaah Dalam Pembentukan Karakter Disiplin Siswa Kelas Atas MI - Didit Darmawan; Nur ‘Aisyatir Rodliyah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The formation of disciplinary character is one of the important objectives of elementary education, particularly in Madrasah Ibtidaiyah (MI) which is based on Islamic values. One strategy widely implemented to instill discipline is the habituation of religious activities in the school environment, especially congregational Dhuha prayer. This study aims to examine the role of congregational Dhuha prayer habituation as a strategy for developing discipline among upper-grade students of Madrasah Ibtidaiyah. This research employed a qualitative method with a literature study approach. Data were collected through a review of scientific articles, national and international journals, and relevant academic works obtained from Google Scholar. A total of ten scientific publications relevant to the research focus were selected and analyzed. Data analysis was conducted using descriptive qualitative techniques by reviewing, comparing, and synthesizing findings from previous studies. The results indicate that the habituation of congregational Dhuha prayer, when implemented regularly and systematically, has a positive effect on the development of student discipline at the upper-grade level of Madrasah Ibtidaiyah. The formed discipline includes time discipline, compliance with school regulations, responsibility, and consistency in learning and religious activities. The effectiveness of this habituation is further strengthened by a religious school culture and the exemplary role of teachers. Therefore, congregational Dhuha prayer habituation can be considered an effective character education strategy for fostering discipline among Madrasah Ibtidaiyah students.